Peripheral Use of Vasopressors in Shock: Clinical Considerations and Recommendations for Use in Obstetrics - Pacheco, Luis D.; Fox, Karin A.; Clifford, Corey C.; Behnia, Faranak; Bauer, Melissa E.; Saad, Antonio F.; Saade, George R. (American Journal of Perinatology, 2024)
This study aimed to evaluate the safety of peripheral administration of vasopressor agents among patients with circulatory shock.We reviewed the published literature evaluating the use of peripheral norepinephrine in patients with shock and proposed a protocol for use in labor and delivery units.Peripheral administration of norepinephrine is a safe and potentially lifesaving intervention for patients in labor and delivery with extremely low complication rates.Adoption of a protocol for peripheral administration of vasopressors in labor and delivery is safe and may prevent life threatening delays in hemodynamic resuscitation.
Keywords: pregnancy; shock; vasopressors; peripheral venous lines